Assessment and Rehabilitation of Oral Feeding Difficulties in Preterm Infants - GUAN Hanyue; CHEN Ling; HUANG Jinyu; TANG Xinqun; LIU Caiwei; ZHU Ruqiao; ZENG Qing (康复学报)
The immaturity of the sucking reflex and swallowing reflex in preterm infants, and the incoordination of suck-swallow-breath (SSWB) patterns lead to feeding problems, such as cough, aspiration, feeding difficulties etc. Therefore, standardized assessment should be carried out for feeding difficulties in preterm infants, and rehabilitation should be involved as early as possible. This article reviewed the studies on the clinical characteristics, current status, evaluation and rehabilitation treatment of feeding difficulties in preterm infants at home and abroad, to provide evaluation and treatment ideas for feeding difficulties in preterm infants. Evaluation of feeding difficulties in preterm infants includes sucking, swallowing, respiratory and SSWB patterns. Sucking pattern assessments include nutritional and non-nutritive sucking assessments; swallowing pattern assessments include oral preparation, swallowing, and esophageal phases assessments; respiratory pattern assessments include typeⅠ, typeⅡ, and type Ⅲ respiratory pattern assessments. SSWB mainly assesses the coordination of sucking, swallowing, and breathing during the feeding process in premature infants. The main evaluation methods include imaging and scale assessment methods. The imaging assessments include video fluoroscopic swallowing study (VFSS), fiberoptic endoscopic evaluation of swallowing (FEES), ultrasound imaging and high-resolution manometry (HRM). The scales assessment includes preterm infant oral feeding readiness assessment (PIOFRA), neonatal oral-motor assesment scale (NOMAS) and oral feeding skills (OFS) scale. Most imaging assessment methods focus on swallowing and sucking patterns, which are more objective and accurate. However, there is a lack of imaging assessment methods in respiratory and SSWB patterns. The scale assessments can provide comprehensive evaluation of sucking, swallowing, respiration and SSWB patterns but are highly subjective. The rehabilitation treatments commonly used in premature infants mainly involve three aspects: sucking, swallowing and respiration. The sucking intervention includes non-nutritive sucking and sensorimotor stimulation, swallowing therapy includes swallowing function training and individualized swallowing therapy, respiratory therapy mainly involves respiratory pattern intervention. In addition, the feeding state and position of feeding should be noted.